2016
DOI: 10.1093/bja/aew343
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen in the initial resuscitation of severe trauma (FiiRST): a randomized feasibility trial

Abstract: Early infusion of FC is feasible and increases plasma fibrinogen concentration during trauma resuscitation. Larger trials are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 41 publications
7
85
0
4
Order By: Relevance
“…FC can be stored in the trauma bay, rapidly reconstituted and administered. The recently published FiiRST trial that reports early FC use is feasible and increases plasma fibrinogen levels during traumatic haemorrhage [40]. The recently completed, but not yet published, E-FIT trial (ISRCTN67540073) investigated empiric fixed-dose FC delivery in severe trauma in addition to standard MHPs, with time to delivery of FC as the primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…FC can be stored in the trauma bay, rapidly reconstituted and administered. The recently published FiiRST trial that reports early FC use is feasible and increases plasma fibrinogen levels during traumatic haemorrhage [40]. The recently completed, but not yet published, E-FIT trial (ISRCTN67540073) investigated empiric fixed-dose FC delivery in severe trauma in addition to standard MHPs, with time to delivery of FC as the primary endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the time to administration of fibrinogen replacement and have compared FC to cryoprecipitate but as yet there have been no large studies powered for patient‐centred outcomes or reduction in blood product usage . Systems that achieve early and rapid fibrinogen replacement generally involve empiric delivery of FC to patients presenting with clinical indications of severe bleeding, not those exclusively with a low fibrinogen level . Empiric, immediate transfusion therapy such as the early coagulation support protocol, which provides FC to patients meeting clinical parameters on presentation and before ROTEM or SLT results, have been able to reduce the administration time to under 30 min .…”
Section: Methodsmentioning
confidence: 99%
“…First, only two trials have been performed to determine the most effective dosing strategy (e.g., fixed dose vs. weight based vs. targeted to a postinfusion fibrinogen level): an RCT in postpartum hemorrhage found no impact of 2 g of fibrinogen, suggesting the minimum required dose is more than 2 g, and a trial in major pediatric surgery found earlier dosing of fibrinogen concentrate (at a higher FIBTEM maximum clot firmness threshold) was more effective in reducing transfusion requirements . Second, the preemptive use of fibrinogen concentrate before or early in the course of hemorrhage has been tested in only several small pilot trials, and a large definitive trial in severe traumatic hemorrhage is under way with cryoprecipitate (CRYOSTAT‐2/ISRCTN14998314). Overall, the preemptive use of fibrinogen before hemorrhage occurs has not been successful .…”
Section: Fibrinogen Concentratementioning
confidence: 99%